Potency of novel oximes to reactivate sarin inhibited human cholinesterases - Jun, Daniel; Kuča, Kamil; Pícha, Jan; Kolečkář, Vít; Marek, Jan (Drug and chemical toxicology, 2008)
Class of monoquaternary pyridinium oximes was in vitro tested as potential reactivators of acetylcholinesterase (AChE; EC 3.1.1.7) inhibited by nerve agent sarin. Human brain homogenate was used as an appropriate source of cholinesterases. Reactivation potency of novel oximes was compared with currently available reactivators - pralidoxime, obidoxime, and HI-6. According to the obtained results, only five reactivators were able to satisfactorily renew cholinesterase potency (pralidoxime, obidoxime, HI-6, 4-PAM, and K119). Unfortunately, none of the novel tested reactivators surpassed the reactivation potency of the currently most promising reactivator, HI-6. This study shows that monoquaternary reactivators are unable to reactivate nerve agent-inhibited AChE. Due to this, in future, only bisquaternary compounds derived from HI-6 or obidoxime should be designed as new potential cholinesterase reactivators.
Keywords: financování organizované; Acetylcholinesterase; antidota; sarin; oximy; Pyridinium Compounds; In Vitro Techniques; Molecular Structure; Sarin; Structure-Activity Relationship; pyridinové sloučeniny; techniky in vitro; lidé; Pralidoxime Compounds; Antidotes; mozek; Financing, Organized; pralidoximové sloučeniny; molekulární struktura; Oximes; Obidoxime Chloride; acetylcholinesterasa; Brain; reaktivátory cholinesterasy; obidoxim chlorid; vztahy mezi strukturou a aktivitou; cholinesterasové inhibitory; Cholinesterase Inhibitors; Cholinesterase Reactivators; Humans